Answer:
f(x) = ( x+2)(x-5)(x-6)
Step-by-step explanation:
We can write the equation with zeros at b1,b2,b3
f(x) =a( x-b1)(x-b2)(x-b3) where a is a constant and b1 b2 b3 are the zeros
f(x) = a( x- -2)(x-5)(x-6)
f(x) = a( x+2)(x-5)(x-6)
We can choose a since we are not given any more information about the function. Let a = 1
f(x) = 1( x+2)(x-5)(x-6)
f(x) = ( x+2)(x-5)(x-6)
Add
$3.45
$3.45
$3.45
$3.45
$3.45
$3.45
$3.45
$3.45
$3.45
$3.45
Answer:
60°
Step-by-step explanation:
angle A +angle B +angle C = 180
30° +B+90°= 180
120°+B=180°
B=180°-120°
B=60°
Answer:
60% x 25
55 % x 25
10 in english
25 is total and rest will be math
so 25-10 = 15
15 students failed math
1_1/3 = 4/3
-3_1/4 = -13/4
(4/3) - (-13/4)
(4/3) + (13/4)
We can see that (4/3) + (13/4) leads to a positive answer.
Answer: choice D